Nonhumans in participatory design. Issue 3 (3rd July 2018) - Rice, Louis
Abstract: This article examines the role that nonhumans play in participatory design. Research and practice concerned with participatory design mostly focuses on human participants, however nonhumans also participate in the design process and can play a significant role in shaping the process. This article focuses on how nonhumans participate in the design process. An empirical case study is used to illustrate how humans and nonhumans assemble to form networks in order to effect a design. Nonhumans increase the level of participation in a design process. The case study reveals how nonhumans help to maintain, destroy or strengthen networks by substituting, mediating and communicating with humans and often, in doing so, making human actors more or less visible in the process. Nonhumans play a part in configuring the social. Revealing the presence and roles of nonhumans is an important means through which to increase the democracy within the design process.